Pengaruh Asal Bahan Setek Terhadap Pertumbuhan Setek Cabang Jeruk Nipis Tanpa Biji (Citrus aurantiifolia Swingle) - Linda E. Lindongi (Fakultas Pertanian Universitas Papua, 2009)
This research has conducted to find out the best position of lime branch used for cutting. Completely randomized block design was used in this present study with three cutting source position such as terminal, middle and apex of branch. Shoot time formation, bud length, leaf number, root length and root number were measured in this experiment. The result of this experiment showed that apex and middle of branch gave cuttings with earlier shoot formation (12 days) compare to terminal part of branch (14 days). In contrast, cuttings from middle of branch showed better result in terms of shoot length,leaf number, root length as well as root number compare to terminal and apex of branch.